Study of applications of content based information Retrieval models in healthcare - SENTHIL MURUGAN BALAKRISHNAN (International Journal of Pharma and Bio Sciences, 2017)
Information Retrieval plays an important role in a distributed collection of documents. In this paper, we discuss the various information retrieval models for an efficient and effective matching. We analyze each and every model for its benefits and issues in its usage in a distributed environment. The models are compared on the basis of the characteristics such as input query, implementation, ranking and precision rate. As the Healthcare industry turns out to be progressively reliant on electronic data the requirement for modern data retrieval frameworks and for educated individuals to plan, buy, and utilize them additionally increments. This paper also analyzes the cases of these information retrieval schemes in the Healthcare sector.